The Role of Attorney As the Guards Team Of Security Government And Regional Development In The Prevention Efforts Of Criminal Corruption (Case Study In State Attorney Of Purworejo) - Sujatmika Sujatmika; Maryanto Maryanto (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2019)
The efforts to overcome of the Corruption by law enforcement can be done by way of prevention (preventive) and prevention (repressive).The problems of this study are: Guards Team Establishment, Security Government and Regional Development in the law enforcement of corruption in the State Attorney of Purworejo. The Role of the Prosecutor as Guards Team of Security Government and Regional Development in the Prevention of Corruption in the State Attorney of Purworejo, a limiting factor of the role of the Prosecutor as Guards Team , Security Government and Regional Development in the Prevention of Corruption in the State Attorney of Purworejo and solutions.This research use socio-juridical approach and specification in this study were included descriptive analysis. The source and type of data in this study are primary data obtained from interviews with field studies Public Prosecutor in the State Attorney of Purworejo, And secondary data obtained from the study of literature relating to the theory of supervision, authority and law enforcement.Based on the results of research that Purpose of establishing of the Guards Team of Security Government and Regional Development, namely: 1) the loss of doubt the power of the budget (KPA), the power of the commitment (KDP), and implementing activities in carrying out its activities, 2) absorption of the budget properly and on time, and 3) development of Purworejo run properly and without corruption. The role of the Attorney divided into three normative role, the ideal role, and the role of factual. Inhibiting factor is the factor of its own law, law enforcement apparatus which is not widely understood rule of law, the factors supporting infrastructure and inadequate facilities, community factors and cultural factors. Solutions to overcome obstacles, namely: a) Prevention / preventive and persuasive, b) Legal Assistance; c) Coordination with APIPs and / or related agencies; d) Conduct Monitoring and Evaluation; and e) The Enforcement of Repressive Laws.Keywords: Attorney; Corruption; Role; Guard Team of Security Government and Regional Development; Crime.